A new approach to the Haigh diagram of sintered steels from unalloyed iron to heat treated conditions. (8th August 2021) - Beiss, P.; Burkamp, K.; Broeckmann, C.
ABSTRACT: Systematic investigations on the fatigue strength of heat treated sintered steels with notched specimens are barely found in the literature, especially at stress ratios other than R  = −1. For that reason a larger study was initiated with the aim to provide a base for safe estimates of fatigue strengths also for heat treated components. This work deals with one possibility to design a Haigh diagram for the positive mean stress range beyond R  = −1. Starting point is a new approach to determine the mean stress sensitivity M . As all equations derived are based on averages, in extreme cases individual test results can deviate by more than 20% from the calculated value. Regularly, however, deviations around ±10% are observed.